Bulan Madu yang Singkat: Mengapa Turki Mengubah Sikapnya terhadap Suriah Sejak Perang Sipil 2011? - Alfiyan Nooryan Putra Pikoli (Department of International Relations, Universitas Andalas, 2021)
The Arab Spring phenomenon has a negative impact on security stability in the Middle East. One of them is triggering the Syrian civil war. The civil war, which was originally a domestic Syrian problem, then escalated to Turkish territory. In the end, it had a bad impact on the relationship between Turkey and Syria, which was good before the civil war began. This paper aims to analyze the causes of the change in Turkey's political attitude towards Syria, and the decision to intervene military in Syria. Previous studies have discussed much of Turkey's role as a peacemaker for the conflict. It did not specifically discuss the reasons behind Turkey's military intervention in Syria. With a securitization theory approach, this article identifies the existential threat factors faced by Turkey. Especially the speech act variable in this theory seeks to analyze the political statement of Turkish authorities. This study uses qualitative methods in providing causal explanations. This article identifies that the various threats faced by Turkey as implications of civil war cannot be separated from the role of the Bashar Assad regime in Syria. The main argument is the Assad regime in Syria is the main root of Turkey's various security problems. However, this article does not measure the effectiveness of Turkey's military approach to the threats it faces in Syria. The theory of securitization has limitations in carrying out this effectiveness analysis.